ANALISIS KUANTITATIF B-KAROTEN DAN UJI AKTTVITAS KAROTENOID DALAM ALGA COKLAT TURBINARIA DECURRENS - Biranti, Fransisca; Nursid, Muhammad; Cahyono, Bambang (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT—One of the Indonesian marine natural resources, brown alga of Turbinaria decurrens, used in pharmacy in order of carotenoid pigment as antioxidant. We interested in analysis B-caroten in Turbinaria decurrens and antioxidant and anti-tumor activity. The method that is use to divide carotenoid is the hierarchy maseration method using n-hexane, ethyl acetate and methanol and then using chromatography column. To analyze the qualitative carotenoid uses HPLC by Crc column and eluenmethanol-acetonitrile (3:I). Meanwhile, the test of bioactivity carotene uses radical DPPH (1I'difenil-2-pibilhidrozil) to test of antioxidant qnd sitotoksik asscy with MTT [3,(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrcaolium bromideJ for HeLa tumor cells to test of anti-tumor. The result of this research is B -caroten thqt is in qctract has 0.00387%. Moreover, bioacttvity test shows that B -caroten fraction does notactive to neutralize of DPPHfree radical than ascorbic aci but it shows the acttvity to kill HeLa tumor cells.Keywords : Turblnaria decunens, Carolenoid, Antioksidan, Antitumor",